Nanoporous Pd with Tunable Pore Size prepared by Dealloying Pd 30Cu40Ni10P20 Metallic Glass and Their Catalytic Performance - Zhu,Kui (2019)
This work reports the formation of nanoprous Pd with tunable pore size and high stability by dealloying Pd30Cu40Ni10P20 metallic glass. The results show that lower dealloying temperature results in smaller pore size while the dealloying duration does not cause distinct change in the porous structure, even at an ambient dealloying temperature. The glassy structure and the multiple components in the precursor alloy are attributed to the hindered diffusion of Pd atoms and a slow coarsening rate of the nanoprous structure. The fully dealloyed porous sample with the smallest average pores size of 10 nm exhibit much higher catalytic activity when compare with the commercial Pd/C catalysts while the specimen with an average pores size of 13 nm shows the highest catalytic stability among the fully dealloyed alloys.